Pulmonary Embolism in a Patient with Behçet’s Disease: A Case Report - Abdelbaki, Mourad; Khellafi, N.; Benmessaoud, D. (International Journal of Innovative Research in Medical Science, 2024)
Behçet syndrome is a systemic vasculitis of unknown etiology, frequently characterized by recurrent oral and genital ulcerations and uveitis. Patients with Behçet syndrome can have both arterial and venous involvement. We report the observation of a case of a 29-year-old man who was admitted with clinical presentation of pulmonary embolism, for whom investigations for the etiology concluded in the diagnosis of Behçet's disease.